Natural control for bee pest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Natural chemicals that draw the parasitic mite, Varroa, away from worker bees have been identified, and French scientists have isolated these chemicals from substances taken from bee larvae. Varroa jacobsoni has been spreading throughout the world...